System Dynamics Development Model for Operations Strategy in Power Generation System through Integrated Transmission and Distribution System - Lilia Trisyathia Quentara; Erma Suryani (IPTEK Journal of Science, 2017)
Electrification Ratio in East Java (Indonesia) has reached 86.67% at the end of 2015 due to in Madura island only 60.55% who have received electricity supply from PLN. The topography of Madura which far-flung distances per village, as well as the small number of households in the village are being constraint in build up the electricity infrastructure investment. The main problem in electrical operating system is how to meet the demand and supply of electric power by maintaining the continuity of effective and efficient services to PLN customers. These problems would take a long-term solution in electrical system which is able to increase the role of renewable energy, improve the reliability, safety and efficiency, reduce energy costs, and can recover quickly from interruptions. Effective and efficient electrical operational systems in real time is expected to improve the sustainability of supply electric power. The Dynamic System method is used to analyze the electrical operating system by developing a scenario model to identify the factors and variables that affect the system, to be use-full as consideration in taking strategic policy in operational PLN